2014
DOI: 10.1167/iovs.13-13041
|View full text |Cite
|
Sign up to set email alerts
|

Objective Assessment of the Corneal Endothelium in Fuchs' Endothelial Dystrophy

Abstract: The effective ECD in confocal images provides an objective means of assessing the corneal endothelium in Fuchs' dystrophy and might be a useful tool in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…Recent studies have reported a method for objectively grading 25,43 or predicting progression of Fuchs' endothelial corneal dystrophy. 44 The peripheral corneal thickness 25 and the central ratio of guttae 43 are especially useful for objective grading.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported a method for objectively grading 25,43 or predicting progression of Fuchs' endothelial corneal dystrophy. 44 The peripheral corneal thickness 25 and the central ratio of guttae 43 are especially useful for objective grading.…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant differences were detected between wound types in regard to the size of CECs, CECs over peeled wounds were less circular than those over scratched wounds, with this difference accentuated by Y-27632 stimulation. Given the clinical observations of cellular pleomorphism and loss of cellular hexagonality associated with in vivo CEC migration and enlargement following acute endothelial cell loss, 24 this disparity in CEC circularity may simply be a reflection of the exaggerated promigratory response mounted by CECs secondary to the potent stimulating effects of Y-27632. Additionally, the forcible migration of CECs over an anatomically unfavorable substrate (bare posterior corneal stroma: peeled wound) under the influence of Y-27632 may possibly have induced greater cellular pleomorphism than that demonstrated by CECs migrating across smooth, CEC-denuded DM (scratched wound).…”
Section: Figurementioning
confidence: 99%
“…22 Disease progression is characterized by an increase in the size and density of guttae 23 and concomitant reductions in the population of healthy CECs. 24 In contrast, pseudophakic bullous keratopathy (PBK) is an acquired corneal endothelial disorder that may occur following intraocular cataract extraction surgery. 25 Various causative factors such as excessive phacoemulsification energy 26 and mechanical trauma 27 to the corneal endothelium during cataract extraction surgery have been implicated in causing stress-induced apoptosis of CECs.…”
mentioning
confidence: 99%
“…We examined the relationships between HOAs, backscatter, and corneal morphologic characteristics that are typically altered in FECD, such as corneal thickness and effective endothelial cell density (ECD e ). 14 We hypothesized that HOAs and backscatter are increased in the anterior and posterior cornea early in FECD, and are associated with ECD e and corneal thickness.…”
Section: Introductionmentioning
confidence: 99%